Edward Arden and the Dudley earls of Warwick and Leicester, c. 1572–1583. Issue 2 (15th September 2016) - Enis, Cathryn
Abstract : Between c. 1572 and his execution in 1583, Edward Arden, a Catholic gentleman from Warwickshire, was involved in a lineage dispute with Ambrose and Robert Dudley, earls of Warwick and Leicester and two of the most powerful men in early modern England, over their shared ancestral claim to a Saxon known as Turchil. This article explores the significance of this dispute from a number of perspectives, including the ancestry of Edward Arden, the history of the Warwick and Leicester earldoms and Philip Sidney's Defense of Leicester, in order to explore lineage as central to the prevailing ideology of power. It uses the clash between Arden and the Dudleys to present an environment in which Catholics were still part of the political mainstream and in which different political discourses led to conflict as well as consensus during the 1570s and early 1580s. Moreover, the article suggests that the activities of the heralds and the pedigrees they produced had a political function during this period which merits changing our approach to an underused manuscript source.